Social awareness of whole grains and the feasibility of replacement with refined grains: A qualitative study - Fatemeh Kazemi (International Journal of Preventive Medicine, 2021)
Background: A correlation between type 2 diabetes and refined carbohydrates has been proven, while several studies have indicated that Iranian daily diets are poor in term of proper carbohydrates. It was thus considered absolutely critical to conduct a qualitative study in terms of people's attitudes toward whole grains, and the feasibility of their replacing existing refined carbohydrates in their diets. The aim of this study is to probe Iranian awareness of whole grains, to explore barriers to refined-grain substitution with whole grains and legumes, and to assess whole-grain sensory perceptions. Methods: Focus group discussions (FGDs) and taste tests conducted between July 2016 and March 2017 in urban and rural areas of Kurdistan, Yazd, and Tehran provinces in Iran. A total of 96 healthy men and women (aged 40-65, BMI ≥25 kg/m2) were selected through purposive sampling with maximum variation. FGDs were categorized by content analysis method. As for taste test, ANOVA analysis with Bonferroni post-hoc was used to determine significant differences (P < 0.05). Results: Four themes and 11 sub-themes emerged. Cultural beliefs, traditional eating patterns, sensory properties, and familial acceptance were the most influential factors in choosing the type of bread and rice. Simultaneously they are the most prominent barriers to consuming whole grains and legumes. Plain cooked brown rice had the lowest mean sensory attribute score and traditional whole-wheat flatbread was the highest. Conclusions: There was a higher acceptance tendency toward using traditional whole-wheat flatbread rather than refined grains, as it was consistent with preference and priority. However, low availability was the largest substitution problem.